First insights into multidisciplinary and multispecialty long COVID networks—a SWOT analysis from the perspective of ambulatory health care professionals - Stengel, Sandra; Gölz, Lea; Kolb, Joachim; Tarbet, Karin; Völler, Stefanie; Koetsenruijter, Jan; Szecsenyi, Joachim; Merle, Uta (Frontiers in Medicine, 2023)
Introduction: Multidisciplinary and multispecialty approaches with central integration of primary care, individualized long-term rehabilitative care, and multidisciplinary care pathways are recommended by international consortia to face the challenges of care of long COVID. Two regional long COVID networks – Rhein-Neckar (RN) and Ludwigsburg (LU) have emerged as ad hoc examples of best practice in Southern Germany. The aim of the community case study is to provide first insights into the experiences of the networks. Methods: The exploratory observational study was conducted between April and June 2023, focusing on an observation period of just under 24 months and using a document analysis supported by MAXQDA and SWOT analysis with ambulatory health care professionals in two online group discussions. Results: The document analysis revealed that both networks have defined network participants who have agreed on common goals and patient pathways and have established ways of communicating, organizing, and collaborating. Both networks agreed on a primary care-based, multidisciplinary and multispecialty approach. The main differences in realization emerged in LU as a focus on the ambulatory setting and very concrete application to individual patients, while RN showed a focus on an intersectoral character with participation of the specialized university hospital sector, knowledge transfer and a supra-regional approach with the involvement of the meso and macro level. The SWOT analysis (n = 14 participants, n = 6 male, 7 physicians (4 disciplines), 7 therapists (5 professions)) showed strengths such as resulting collaboration, contribution to knowledge transfer, and improvement of care for individual patients. As barriers e.g. lack of reimbursement, high efforts of care, and persistent motivation gaps became apparent. Potentials mentioned were e.g. transferability to other diseases such as Myalgic Encephalomyelitis/ Chronic Fatigue Syndrome, promotion of addressing a "difficult topic" and promotion of intersectoral care concepts; risks mentioned were e.g. limited network resources and negative effects on the development of other structures. Conclusion: Resulting implications for practice and research address a call to policy makers and funders to support further research to find out what generalizable results regarding usefulness, effectiveness, and efficiency including transferability to other post-infectious diseases can be derived.